Analisis Aliran Kas Operasi, Book Tax Differences, Ukuran Perusahaan Dan Tingkat Hutang Terhadap Persistensi Laba - ., Jasmar; Jasmar, Jasmar; Yuliana, Riska (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
This research was aim to analyzing the influence of operating cash flow, Book Tax Differences, company size, debt level on the earnings persistence at property company, real estate and building construction which in Indonesia Stock Exchange 2013-2017. The sample collection method using purposive sampling, with predetermined criteria and a total sample of 21 companies. This quantitative research uses panel data regression analysis with Eviews application tool version 10. Simultaneously, operating cash flow, book tax differences, company size, and debt level have an effect on earnings persistence with a probability value of 0.021120 <0.05.While the coefficient of determination (R2), the independent variable can explain the effect of earnings persistence of 50.07%, while the remaining 49.93% is explained OUT of the variables studied.